Film composition & method thereof - Lai, Oi Ming (2014)
The present invention discloses a composition for use as a film comprising a balanced blend of lipid, polymer, plasticizer, polysaccharide, surfactant and water, having antimicrobial and antioxidant properties. The lipid useful in the film composition includes edible fats and oils derived from palm, which includes red palm olein, as well as refined, bleached and deodorised palm oil. The red palm olein and refined, bleached and deodorised palm oil can be further blended with other oils, which include corn oil, sunflower oils, safflower oil, coconut oil, canola oil, grape seed oil, flax seed oil, sesame oil, rice bran oil, and other oils extracted from herbs and spices or combination thereof. In an embodiment, the composition is in the form of a liquid or plastic dispersion having a viscosity ranging from 5000 to 20000 mPas (cps) at 80°C, allowing the composition to be included in food preparations. In another embodiment, the composition is provided in the form of thermally reversible pellets, powders granules, sheets or solid blocks that are heated at 30 to 120ºC for use in preparing an edible film.